DESCRIPTION OF SMKN6 BANDUNG AUTOMOTIVE LIGHT VEHICLE STUDY PROGRAM STUNDENT’S WORK INTERESTSAND MOTIVATIONASTECHNICIAN - Aliyah, Dewi; Sukrawan, Yusep; Permana, Tatang (Journal of Mechanical Engineering Education, 2020)
This study purpose to find out the work interest and motivation as a technician in AutomotiveLight Vehicle Engineering students. The method used in this study is descriptive method with aquantitative approach. The study was conducted to students of XII Light Vehicle Engineeringclass at SMK Negeri 6 Bandung with a population of 195 data. The sample used in the study is131 people with an error rate of 5%. Data collection techniques in this study used questionnaires,which were distributed to all respondents. The data obtained were analyzed using MicrosoftExcel assistance to get for percentages of work interest and motivation as technicians in students.The results obtained from this study, that Automotive Light Vehicle Engineering students atSMK 6 Bandung have an interest in work as technicians who belong to the high category. Thiscan be seen from the percentage of work interest as a technician which shows that almost allstudents have a work interest as technicians. Based on the results of this study, the teachers arewilling to give directions or solutions for students who have interest and motivation in work astechnicians in order that they can arrange steps to get a job as technicians.